2016
DOI: 10.11157/anzswj-vol23iss3id157
|View full text |Cite
|
Sign up to set email alerts
|

Crossing borders: key features of migrant social workers in New Zealand

Abstract: The emergence of a mobile, professional social work workforce, successfully managing the demands of service-users, policy makers and the public at large in different countries across the globe, provides unprecedented opportunities for professional border-crossing. It is timely to generate New Zealand-specific data on professionals employed in the social services workforce in New Zealand so as to inform educational and institutional responses to this complex phenomenon. A study that seeks to develop a profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The fact that unemployment is high in South Africa might also impact on skilled foreigners' work experience (Kalitanyi & Visser, 2010;Mamabolo, 2015;Di Paola, 2012). The findings in this study support those of a previous study in New Zealand by Bartley et al (2011), which shows that workplace discrimination, exclusion and the economic exploitation of immigrants is a worldwide phenomenon that is not peculiar to South Africa. The violation of rights of skilled professionals outside their countries of origin is a negative phenomenon worldwide despite the contributions that they might be making to the economy of the country of resettlement.…”
Section: Hostility In Practice Communitysupporting
confidence: 82%
See 1 more Smart Citation
“…The fact that unemployment is high in South Africa might also impact on skilled foreigners' work experience (Kalitanyi & Visser, 2010;Mamabolo, 2015;Di Paola, 2012). The findings in this study support those of a previous study in New Zealand by Bartley et al (2011), which shows that workplace discrimination, exclusion and the economic exploitation of immigrants is a worldwide phenomenon that is not peculiar to South Africa. The violation of rights of skilled professionals outside their countries of origin is a negative phenomenon worldwide despite the contributions that they might be making to the economy of the country of resettlement.…”
Section: Hostility In Practice Communitysupporting
confidence: 82%
“…Studies in South Africa have focused on the experiences of unskilled migrants and the challenges that they face (Crush & William, 2003;Everett, 2011;Neocosmos, 2010). However, studies on skilled migrants by Bartley et al (2011), Evans et al (2006) and Castles and Miller (2003) indicate that migrants make positive contributions to the economies of countries of resettlement, yet this rarely gets recognition and their contributions are mostly perceived negatively.…”
Section: Introductionmentioning
confidence: 99%
“…A social worker mobility research team based at the University of Auckland has conducted prior mixed methods studies of the overseas qualified workforce in Aotearoa New Zealand (Bartley, Beddoe, Fouch é, & Harington, 2012), experiences of migrant social workers in Aotearoa New Zealand (Bartley & Beddoe, 2018;Bartley et al, 2011;Fouché, Beddoe, Bartley, & de Haan, 2013; Fouch é, Bartley, Beddoe, & Brenton, 2013;Fouché, Beddoe, Bartley, & Parkes, 2015) and a small qualitative study of Aotearoa New Zealand social workers currently practising in the United Kingdom (UK) and Ireland (Beddoe & Fouché, 2014). Findings of the previous research have concluded that practising social work in a new context creates challenges and opportunities.…”
Section: Abstract: Transnational Social Workers; Global Workforce Mobmentioning
confidence: 99%
“…Findings of the previous research have concluded that practising social work in a new context creates challenges and opportunities. Given the breadth of approaches and models of employment in social work across the globe and its accordingly distinctive shape in specific national settings, many elements of professional practice -for example supervision, pre-and post-qualifying education -are likely to be very different across these diverse contexts (Bartley et al, 2011;Beddoe et al, 2011).…”
Section: Abstract: Transnational Social Workers; Global Workforce Mobmentioning
confidence: 99%
“…into the motivations and experiences of internationally recruited doctors, teachers and nurses (and 2 others in allied health and care professions), as well as social workers (Lyons and Littlechild, 2006;Walsh et al, 2010;Bartley et al, 2011). Indications from some of this literature are that transnational social workers may share similarities, in both motivation and experiences, with these other occupational groups (for example, Winkleman Gleed, 2006;Williams and Balaz, 2008;Guo and Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%